Sero-epidemiology of Syphilis in a Tertiary Teaching Hospital in Kuala Lumpur - Wahab, Asrul Abdul; Ramli, Mohd Ezri Asyraf; Mustafa, Risq Atiqah Munirah; Lim, Grace Min Wen; Sahimi, Wan Nurfatin Wan; Husyairi, Harunarashid; Rahman, Md Mostafizur (Bangladesh Journal of Medical Science, 2018)
Background: Syphilis is common and resurgences predominantly occurs among men who have sex with men (MSM). Objective: The aim of the study was to describe the epidemiology, clinical and serological aspects of patients with syphilis diagnosed at Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Methods: A retrospective study was conducted whereby patients with serologically confirmed syphilis cases between January 2010 and December 2012 were included. The epidemiological and clinical data were gathered from the patient’s progress note. Results: A total of 67 patients were selected in this research (41 males, 26 females). The mean age was 48.97 ± 17.45, where majority were from 20 to 39 years old (37.3%). Most patients were diagnosed at latent stage (65.7%). Identified risk factors for syphilis infection included sexual promiscuity either homosexual or heterosexual, intravenous drug user and partner diagnosed as syphilis. Penicillin is the antibiotic of choice for the treated cases. Conclusions: This study managed to provide an epidemiological and serological data of syphilis infection in our medical center where syphilis was diagnosed predominantly in male especially in young adults. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.62-66